RANCANG BANGUN DAN ANALISA SISTEM TRANSMISI PADA MESIN PENGHALUS KOTORAN KAMBING DENGAN KAPASITAS 50KG/JAM - Ferdiansyah Ferdiansyah (Politeknik Negeri Bengkalis, 2022)
Goat dung grinding machine, the manufacture of this tool serves to facilitate farmers in refining goat dung, after doing the next stage is planning. Drawing planning, calculations to determine the components to be used. The final stage is the manufacturing or assembly process. With the goat dung smoothing tool for farmers designed with a capacity of 50 kg/hour, where this tool has 4 straight blades, it is expected to be able to smooth goat dung quickly. And from the results of the tests carried out, the maximum results are obtained, namely at a speed of 2800 Rpm with a time of 27 minutes where the results are very satisfying, namely the form of smooth results.